Political polarization through political memes for new voters in the 2024 presidential election - Widyaningsih, Winda; Ramadhani, Rizky Wulan; Prihantoro, Edy (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
New voters aged 17 to 24, categorized as Generation Z, are highly proficient in digital technology and actively use social media as a primary source of political information, particularly through political memes. Social media fosters an echo chamber effect by continuously presenting similar political content, reinforcing existing beliefs and contributing to political polarization. This study examines the phenomenon of political polarization among new voters in the 2024 presidential election through political memes, utilizing the Elaboration Likelihood Model (ELM) and the echo chamber concept as theoretical frameworks. A qualitative approach was employed, incorporating in-depth interviews with new voters who rely on social media for political information, content analysis of political memes on social media platforms, and a literature review. The findings indicate that new voters predominantly engage with political information through the central route of processing, relying on news portals, social media, and interpersonal discussions. However, social media algorithms reinforce an echo chamber effect by curating content based on users' previous interactions, leading to the polarization of supporters of different candidates (01, 02, and 03). This polarization manifests in heated debates and conflicts, particularly in the comment sections of social media posts featuring political memes. The subjective interpretation of memes—often infused with humor, satire, or sarcasm—exacerbates tensions, as they are perceived as either excessively supportive of or hostile toward particular candidates, further intensifying political divisions.